Rażąca niesprawiedliwość orzeczenia w polskim postępowaniu karnym jako specyficzna przyczyna odwoławcza - Sobiech, Jan ("Młody Jurysta" Czasopismo Studentów i Doktorantów Wydziału Prawa i Administracji UKSW, 2017)
The institution of gross unjust judgement in the Polish criminal proceedings operates as a specific condition for appeal in art. 440 of the Code of Criminal Procedure. It has not been defined on the basis of laws because a key role in its interpretation has judicatory with some support from the doctrine of law. The application of this provision takes place in the case of the operation of the gross unjust judgment, but which cannot be repealed because of the relative or absolute causes of appeal. The court has to assess whether a particular breach has a blatantly unfair character, often making use of the general clauses like “social justice” or “principles of social coexistence”. The regulation of art. 440 of Code of Criminal Procedure undoubtedly contributes to the removal from legal circulation of defective judgments that cannot be waived if the parties could move only within the limits set by their appeal.